1990
DOI: 10.1039/dt9900002081
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional phosphoric acid–phosphine oxide extractants: synthesis and complexes with uranium-(IV) and -(VI) and iron(III)

Abstract: A bifunctional extractant (H L) carrying phosphine oxide and phosphoric acid complexing centres has been synthesized by the cyclic enediol phosphate method, using a two-step reaction with dihexyl (hydroxymethy1)phosphine oxide and 2-ethylhexanol. The bifunctional complexant complexes both UIv and Uv'. The complexation process, as shown by 31P n.m.r. spectroscopy, involves both the R3P=0 and (R'O),PO,H centres ( R=C6H,3, R' =C,H,,).The compound H L exists as hydrogen-bonded associates in the organic (hexane) ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The starting compounds: o -anisylphenylphosphine oxide, (1-naphthyl)phenylphosphine oxide, di- p -anisylphosphine oxide, di- p -fluorophenylphosphine oxide, di- p -tolylphosphine oxide, di(3,5-dimethylphenyl)phosphine oxide, tert -butylphenylphosphine oxide, benzylphenylphosphine oxide, phenyl(isopropyl)phosphine oxide, cyclohexylphenylphosphine oxide, di- c -hexylphosphine oxide, di- n -hexylphosphine oxide, methylphenylphosphine oxide, diphenylphosphine oxide, tert -butylmethylphenylphosphine oxide, and optically active tert -butylphenylphosphine oxide were prepared according to reported methods. Optically active o -anisyl(2-hydroxyethyl)phenylphosphine oxide was available from another studies…”
Section: Methodsmentioning
confidence: 99%
“…The starting compounds: o -anisylphenylphosphine oxide, (1-naphthyl)phenylphosphine oxide, di- p -anisylphosphine oxide, di- p -fluorophenylphosphine oxide, di- p -tolylphosphine oxide, di(3,5-dimethylphenyl)phosphine oxide, tert -butylphenylphosphine oxide, benzylphenylphosphine oxide, phenyl(isopropyl)phosphine oxide, cyclohexylphenylphosphine oxide, di- c -hexylphosphine oxide, di- n -hexylphosphine oxide, methylphenylphosphine oxide, diphenylphosphine oxide, tert -butylmethylphenylphosphine oxide, and optically active tert -butylphenylphosphine oxide were prepared according to reported methods. Optically active o -anisyl(2-hydroxyethyl)phenylphosphine oxide was available from another studies…”
Section: Methodsmentioning
confidence: 99%
“…Diphenylphosphine oxide ( 11a ), bis- p -anisylphosphine oxide ( 11b ), bis- o -tolylphosphine oxide ( 11c ), di- c -hexylphosphine oxide ( 11d ), di- n -hexylphosphine oxide ( 11e ), bis-1-naphthylphosphine oxide ( 11f ), bis- p -tolylphosphine oxide ( 11g ), o -anisylphenylphosphine oxide ( 11h ), optically active ( R P )- tert -butylphenylphosphine oxide (( R P )- 21 ), and optically active ( R P )- tert -butylphenylmethylphosphine oxide (( R P )- 14 ) were synthesized according to reported procedures. Diphenylphosphine was commercially available and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…A bifunctional compound, O -methyldihexylphosphine oxide O ‘-hexyl-2-ethylphosphoric acid, that possesses the properties of the two components of the above synergistic mixture in one entity has been prepared. The linking of phosphine oxide and phosphate groups in the same molecule has resulted in an enhancement of the extraction capabilities (8.7 times stronger), due to the formation of a bimolecular complex (i.e., the extraction mechanism steps are simpler) . The synergistic effect of the two moieties of the molecule has been demonstrated as well by 31 P NMR, where it was observed that both phosphorus ligands participate in the complexation . This new reagent shows a considerable advantage in the extraction of U(VI) over synergistic mixtures of extractants in solvent extraction processes.…”
mentioning
confidence: 96%
“…The mechanism of the synergistic extraction involves the formation of a trimolecular complex TOPO−UO 2 −D-2EHPA, where TOPO is responsible for pulling UO 2 2+ from the aqueous phase, and D-2EHPA improves the solubility of the complex in the organic phase . A bifunctional compound, O -methyldihexylphosphine oxide O ‘-hexyl-2-ethylphosphoric acid, that possesses the properties of the two components of the above synergistic mixture in one entity has been prepared. The linking of phosphine oxide and phosphate groups in the same molecule has resulted in an enhancement of the extraction capabilities (8.7 times stronger), due to the formation of a bimolecular complex (i.e., the extraction mechanism steps are simpler) . The synergistic effect of the two moieties of the molecule has been demonstrated as well by 31 P NMR, where it was observed that both phosphorus ligands participate in the complexation .…”
mentioning
confidence: 99%
See 1 more Smart Citation